Ruptured abdominal aortic aneurysm: epidemiology, predisposing factors, and biology - Schmitz-Rixen, Thomas; Hakimi, Maani; Peters, Andreas; Böckler, Dittmar (Langenbeck's archives of surgery, 2016)
PurposeAbdominal aortic aneurysm is a common degenerative vascular disorder associated with sudden death due to aortic rupture. This review describes epidemiology, predisposing factors, and biology of ruptured abdominal aortic aneurysms (rAAAs).MethodsBased on a selective literature search in Medline (PubMed), original publications, meta-analyses, systematic reviews, and Cochrane reviews were evaluated for rAAA.ResultsThe hospital admission rate for rAAA is decreasing and is now in the range of approximately 10 per 100,000 population in men. Smoking contributes to about 50 % of population risk for rupture or surgically treated AAA. AAA rupture is a multifaceted biological process involving biochemical, cellular, and proteolytic influences, in addition to biomechanical factors. AAA rupture occurs when the stress (force per unit area) on the aneurysm wall exceeds wall strength. Proteolytic activities of matrix metalloproteinases have been implicated in aneurysm wall weakening and rupture. Aneurysm diameter is the most prominent predisposing factor for aneurysm growth and rupture. Wall stress, aneurysm shape and geometry, intraluminal thrombus, wall thickness, calcification, and metabolic activity influence the rupture risk.ConclusionThe best conservative option to avoid AAA rupture consists in smoking cessation and control of hypertension. Many biological factors influence rupture risk.